THE BIOACCUMULATION OF Cd(II) IONS On Euchema Cottoni SEAWEED BIOAKUMULASI ION Cd(II) PADA RUMPUT LAUT Euchema Cottoni - Indah Raya; Rahmah Rahmah (Hasanuddin University, 2012)
Cadmium is an element that can accumulated in seaweed thallus. One of an alternative methode was used to determine the amount of Cd(II) ions were accumulated in Euchema Cottoni thallus is adsorption methode, that was conducted with variations of contact time and concentrations. The concentrations of Cd(II) ions in solutions were determined by using Atomic Absorption Spectrophotometer (AAS). Isothermal model to evaluated the maximum adsoprtions capacity were used Freundlich and Langmuir isotherms. Based on both isothermal models the results showed that adsorption capacity were 33,898 mg/g wet weight by Langmuir and 0,00625 mg/g wet weight by Freunlich isotherms respectively. The adsorptions energy (ΔG) is 9,7482 KJ/mol indicated as physisorptions. While infrared spectrum showed Euchema cottoni have –OH, CO2, -CH2, -CH3, and - SO3- functional groups.